Management of Juvenile idiopathic arthritis-associated uveitis duringthe COVID-19 pandemic in a pediatric referral center in Lombardy. (16th November 2020) - Miserocchi, Elisabetta; Giuffrè, Chiara; Modorati, Giulio M.; Cimaz, Rolando
ABSTRACT: Italy was the first European country to be affected by the SARS-CoV-2 pandemic. In this scenario, we had to face a new clinical approach in our Pediatric Rheumatology Unit for the management of patients affected by juvenile idiopathic arthritis (JIA)-associated uveitis. During the lockdown (phase 1), the weekly outpatient clinic was discontinued and telephone consultations were set up. A toll-free telephone number was instituted for emergencies. None of our children with JIA-associated uveitis was advised to stop the ongoing immunosuppressant systemic therapy. We had no cases of COVID-19 infection and uveitis activity was under control in all but two out of 125 patients, which was comparable with the pre-COVID-19 situation. During phase 2 of the pandemic, hospital and ambulatory rearrangements were made to minimize the risk of SARS-CoV-2 infection. Overall, during the first 4 weeks of phase 2, we did not notice an increased number of patients with uveitis activity.